2018
DOI: 10.1177/0890117118805060
|View full text |Cite
|
Sign up to set email alerts
|

How Low-Income Smokers in New York Access Cheaper Cigarettes

Abstract: To understand the tobacco acquisition practices of low-income smokers in New York State in light of high cigarette prices due to high cigarette taxes. Design: Eight focus groups with low-income smokers were conducted in spring 2015 and 2016 (n ¼ 74). Setting: New York City (NYC) and Buffalo, New York. Participants: Low-income adults aged 18 to 65 who smoke cigarettes regularly. Method: Qualitative analysis of focus group transcripts that explored differences and similarities by region. We used the interview gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Evidence that illicit product purchases tended to be sporadic, according to availability, contrasts with international studies reporting more established sources of illegally imported tobacco. 39–41 Qualitative studies from the United States and United Kingdom found participants had high awareness of illicit tobacco, which was widely available in communities experiencing greater deprivation. 39–41 For example, Stead et al found illicit trade had become normalized via “fag houses”; although black market tobacco was of lower quality, the purchase process was easy and safe to navigate, and both buyers and sellers benefitted from the arrangement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence that illicit product purchases tended to be sporadic, according to availability, contrasts with international studies reporting more established sources of illegally imported tobacco. 39–41 Qualitative studies from the United States and United Kingdom found participants had high awareness of illicit tobacco, which was widely available in communities experiencing greater deprivation. 39–41 For example, Stead et al found illicit trade had become normalized via “fag houses”; although black market tobacco was of lower quality, the purchase process was easy and safe to navigate, and both buyers and sellers benefitted from the arrangement.…”
Section: Discussionmentioning
confidence: 99%
“… 39–41 Qualitative studies from the United States and United Kingdom found participants had high awareness of illicit tobacco, which was widely available in communities experiencing greater deprivation. 39–41 For example, Stead et al found illicit trade had become normalized via “fag houses”; although black market tobacco was of lower quality, the purchase process was easy and safe to navigate, and both buyers and sellers benefitted from the arrangement. 40 By contrast, U.S. illicit tobacco users sourced products from known and established retailers, and preferred to avoid casual “hookups” with street sellers who typically sold lower quality and less palatable tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maßnahme ist, dass eine Segmentierung des Marktes in preiswerte Discounterzigaretten und teure Markenzigaretten vermieden werden muss, damit kein Markenwechsel in das untere Preisniveau resultiert 26,[136][137][138]. Gligorić et al weist darauf hin, dass Preisänderungen abhängig von der sozialen Schicht unterschiedliche Auswirkungen auf die Tabakprävalenz als auch auf dessen Konsum haben 139.…”
unclassified